Pulmonary Function Abnormalities and Asthma Are Prevalent in Children with Sickle Cell Disease and Are Associated with Acute Chest Syndrome. (1st November 2013) - Intzes, Stefanos; Kalpatthi, Ram V.; Short, Robert; Imran, Hamayun
<x xml:space="preserve">Abstract</x> Pulmonary diseases form major sources of morbidity and mortality in children with sickle cell disease (SCD). The objective of the study was to determine the prevalence of lung function abnormalities and asthma and their association with acute chest syndrome (ACS) in children with SCD. This was a cross-sectional retrospective study of 127 children with SCD; we collected information regarding ACS and asthma and pulmonary function test (PFT) data. Based on PFT results, the patients were assigned to one pattern of lung function [normal, obstructive lung disease (OLD), restrictive lung disease (RLD)]. Statistical analyses included Pearson correlation, prevalence odds ratio (POR), cross-tabulation, and multiple binary logistic regression. OLD was noted in 35% and RLD in 23% of the patients, with the remainder exhibiting a normal PFT pattern. Forty-six percent of patients had asthma, 64% of whom had a history of ACS. OLD (r = .244, P = .008, POR = 2.8) and asthma (r = .395, P < .001, POR = 5.4) were significantly associated with a history of ACS. There was a negative correlation between having normal PFT data and a history of ACS (r = −.289, P = .002, POR = .3). Asthma and pulmonary function abnormalities are prevalent in children with SCD, with OLD being more common than RLD. There is an association between asthma, OLD, and ACS, however causality cannot be proven due to the study design. We stress the importance of actively investigating for a clinical diagnosis of asthma in all patients with SCD and suggest that PFT data may help detect patients at lower risk for ACS.